Evidence for Ca2+ Regulated Magnesium ATPase of Thrombosthenin (Platelet Actomyosin) - Mahendran, C (Thrombosis and Haemostasis, 1974)
The isolation of an actomyosin-like protein from platelets with a Ca2+ sensitive component is described. The addition of 1 mM EGTA results in approximately 40% and 75% inhibition of the Mg-ATPase activity depending on the mode of isolation. The inhibition can be released by a free Ca2+ concentration of 3×l0-6 M. Superprecipitation is also inhibited by 1 mM EGTA and restored in the presence of 10-5 M free Ca2+.